Penegakan Hukum atas Tindak Pidana Penelantaran Anak di Wilayah Ciamis Dihubungkan dengan Undang-Undang Nomor 35 Tahun 2014 tentang Penelantaran Anak (Studi Putusan: Putusan Nomor 238/Pid.Sus/2024/PN Cms) - Erus Rusman; Yuyut Prayuti (Jurnal Hukum Lex Generalis, 2025)
This research examines the effectiveness of law enforcement regarding child neglect crimes in Ciamis Regency, referring to Decision Number 238/Pid.Sus/2024/PN CMs. The analysis employs human rights theory, effectiveness theory, and law enforcement theory. Findings indicate that enforcement remains suboptimal due to structural, cultural, and substantive barriers, although the Ciamis District Prosecutor’s Office has made humanistic and child-centered efforts. The research highlights the necessity of harmonizing legal norms with human rights–based enforcement policies to ensure justice and protection for children.